The Role of BRICS Countries in Global Cooperation and Contribution to World Economic Stability - Dies Nurhayati; Muhammad Syarifuddin Ahzab; Ninik Sudarwati (Digital Innovation : International Journal of Management, 2025)
This study examines the role of BRICS—an intergovernmental organization consisting of Brazil, Russia, India, China, and South Africa—in fostering global cooperation and contributing to world economic stability. BRICS was founded as a strategic response to the dominance of Western financial institutions such as the International Monetary Fund (IMF) and the World Bank, which have long been criticized for their unequal representation and decision-making processes favoring developed economies. In this context, BRICS provides an alternative financial architecture through the creation of the New Development Bank (NDB) and the Contingent Reserve Arrangement (CRA), both of which serve as instruments to support development financing and ensure financial security for its members. Grounded in the frameworks of constructivism and soft power diplomacy, BRICS emphasizes the principles of equality, mutual respect, sustainable development, and South-South cooperation. These values are reflected in its policies and initiatives that prioritize inclusivity, fair participation, and collective growth, especially for developing nations often marginalized in the global economic order. By representing more than 40% of the world’s population and contributing approximately 23% of global GDP, BRICS demonstrates its capacity to shape the international system and establish a more balanced distribution of power and resources. This research employs a qualitative descriptive approach based on secondary data, which is analyzed narratively to highlight the evolving dynamics of BRICS within the global economy. The findings indicate that BRICS has significant potential to challenge Western economic hegemony, enhance economic solidarity among emerging markets, and provide developing countries with greater opportunities for growth and cooperation. Ultimately, BRICS emerges not only as a counterweight to established global institutions but also as a transformative actor capable of reshaping the trajectory of international economic governance in the future.